(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2019)
Concept of bulk material and complexity of storing it are explained. The dependence between the physical and mechanical properties of the loose material and type of construction in which it is stored. Structural elements considered silos and silos with conical and flat bottom are described. The common characteristics of metal silos for bulk materials are given. The classification of metal silos by type of housing design is given. The advantages and disadvantages of silos are described. The possibility of storage of bulk materials in cylindrical shells is analyzed depending on the type of construction. The history of occurrence of structures of spiral-fold silos is considered. The set of equipment for the construction of the housing of the spiral-fold silos is given, the step-by-step process of formation of the folding lock and features of the installation process are presented. The analysis of the structure is made and the advantages and disadvantages of spiral-fold silos are determined.